Semi-fragile digital speech watermarking for online speaker recognition - Nematollahi, Mohammad Ali; Akhaee, Mohammad Ali; Syed Mohamed, Syed Abdul Rahman Al-Haddad; Rosales, Hamurabi Gamboa (Springer, 2015)
In this paper, a semi-fragile and blind digital speech watermarking technique for online speaker recognition systems based on the discrete wavelet packet transform (DWPT) and quantization index modulation (QIM) has been proposed that enables embedding of the watermark within an angle of the wavelet’s sub-bands. To minimize the degradation effects of the watermark, these sub-bands were selected from frequency ranges where little speaker-specific information was available (500–3500 Hz and 6000–7000 Hz). Experimental results on the TIMIT, MIT, and MOBIO speech databases show that the degradation results for speaker verification and identification are 0.39 and 0.97 %, respectively, which are negligible. In addition, the proposed watermark technique can provide the appropriate fragility required for different signal processing operations.